2017
DOI: 10.1104/pp.17.00673
|View full text |Cite
|
Sign up to set email alerts
|

Balance between Cytosolic and Chloroplast Translation Affects Leaf Variegation

Abstract: The development of functional chloroplasts relies on the fine coordination of expressions of both nuclear and chloroplast genomes. We have been using the Arabidopsis () () leaf variegation mutant as a tool to dissect the regulation of chloroplast development. In this work, we screened for genetic enhancer modifiers termed () mutants and report the characterization of the first locus, We showed that encodes the cytosolic 80S ribosome 40S small subunit protein RPS21B and the loss of causes the enhancement of lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 69 publications
2
52
0
Order By: Relevance
“…The cDNA encoding full-length TaWRKY46 without the stop codon was inserted into the pTF486-GFP vector [54] after it was cloned by PCR using specific primers ( Supplementary Table S2) with BamHI restriction site. Wheat leaf protoplasts were isolated from 10-day-old seedlings according to the method of Shan [55].…”
Section: Subcellular Localization Analysis Of Tawrky46mentioning
confidence: 99%
“…The cDNA encoding full-length TaWRKY46 without the stop codon was inserted into the pTF486-GFP vector [54] after it was cloned by PCR using specific primers ( Supplementary Table S2) with BamHI restriction site. Wheat leaf protoplasts were isolated from 10-day-old seedlings according to the method of Shan [55].…”
Section: Subcellular Localization Analysis Of Tawrky46mentioning
confidence: 99%
“…Multiple genetic screens for var2 suppressors in several laboratories have revealed that many suppressors of var2 are genetic factors involved in chloroplast transcription, translation and post-translational turnover. Comprehensive genetic analyses with var2 suppressors defective in chloroplast translation have established that the enhancement of var2 leaf variegation by cytosolic ribosomal protein mutants depends upon chloroplast translation (Wang et al 2018).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Recent evidence suggests that changes in cytosolic translation may have strong genetic interactions with plastid proteostasis machinery. Specifically, mutation of a cytosolic ribosome subunit was shown to enhance variegation phenotypes in thylakoid FtsH mutants (Wang et al, 2018). Given that disruption of plastid translation can suppress these same phenotypes (Yu et al, 2008;Liu et al, 2010;Zheng et al, 2016), it appears that ribosomes in both compartments play a key role in maintenance of plastid-nuclear stoichiometric balance.…”
Section: Network Of Cofunctional Proteins Are Connected Via Their Inmentioning
confidence: 99%